2016
DOI: 10.46792/fuoyejet.v1i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Cybercrimes in Nigeria: Analysis, Detection and Prevention

Abstract: Over the years, the alarming growth of the internet and its wide acceptance has led to increase in security threats. In Nigeria today, several internet assisted crimes known as cybercrimes are committed daily in various forms such as fraudulent electronic mails, pornography, identity theft, hacking, cyber harassment, spamming, Automated Teller Machine spoofing, piracy and phishing. Cybercrime is a threat against various institutions and people who are connected to the internet either through their computers or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…Around 14.6% indicated that they received a text message (SMS) requesting that they urgently provide their bank account information, and that money was withdrawn from their account after providing the account information. This is consistent with the findings of [16], who reported that the majority of their respondents were victims of cyber-attacks after disclosing their banking information via text messages. Around 7.9% of respondents reported receiving a call from an unknown person claiming to be a bank customer representative, requesting their bank account information, which was subsequently provided, and money was withdrawn from their accounts.…”
Section: B Cyber Risks Experienced By the Female Heads Of Farm Househsupporting
confidence: 91%
“…Around 14.6% indicated that they received a text message (SMS) requesting that they urgently provide their bank account information, and that money was withdrawn from their account after providing the account information. This is consistent with the findings of [16], who reported that the majority of their respondents were victims of cyber-attacks after disclosing their banking information via text messages. Around 7.9% of respondents reported receiving a call from an unknown person claiming to be a bank customer representative, requesting their bank account information, which was subsequently provided, and money was withdrawn from their accounts.…”
Section: B Cyber Risks Experienced By the Female Heads Of Farm Househsupporting
confidence: 91%
“…Nigeria has also passed anticybercrime legislation, the Cybercrime Act, 2015 (Mohammed, Mohammed, andSolanke 2019). However, Nigeria appears to be severely under-resourced in terms of being able to cope with cybercrime and financial crime investigations (INTERPOL 2018h;Omodunbi et al 2016), making it fertile ground for offenders and a place where the increasingly online population may find itself at risk of being victimised from domestic or regional offenders.…”
Section: Cybercrimementioning
confidence: 99%
“…Cybercrimes have been defined as fraudulent activities carried out with the use of computers, the internet and other IT devices, hence the crime is digital in nature (Okeshola and Adeta, 2013). Omodunbi et al (2016) identified the forms of cybercrimes as fraudulent electronic mails, impersonation, identity theft, blackmail, forgery, cyber harassment, hacking, spamming, automated teller machine (ATM) spoofing, piracy and phishing. Broadhurst et al (2014) proposed a framework for tracking the evolution of the organisational forms that cybercrimes take to mitigate cybercrime occurrences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cybercrimes have been defined as fraudulent activities carried out with the use of computers, the internet and other IT devices, hence the crime is digital in nature (Okeshola and Adeta, 2013). Omodunbi et al (2016) (Ali et al, 2017;Malik and Islam, 2019). However, as good as this may sound, it is not without a challenge: the transformation comes with new risks and vulnerabilities that could undermine the digital advancement and transformation.…”
Section: Literature Reviewmentioning
confidence: 99%